2021
DOI: 10.1108/sasbe-11-2020-0174
|View full text |Cite
|
Sign up to set email alerts
|

Contractors' adaptation to environmentally sustainable construction: a micro-level implementation framework

Abstract: PurposeThere is low adoption rate of existing environmentally sustainable construction frameworks. Contractors have dwindled capability to adapt to environmentally sustainable construction (ESC) towards achievement of SDGs. The aim of this paper is to develop a framework that leverages both theoretical and practical aspects of sustainable construction to enable contractors' adaptation to ESC at the micro level.Design/methodology/approachDue to the social constructivism orientation of the objectives of this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition, Ahiabor (2019) also revealed that SBC needs better understanding by professionals to create a clear opportunity for real estate and developer adoption. Mensah (2016) also opined that awareness of smart buildings by professionals is still low because of a lack of knowledge on how to execute the concept of smart buildings, which is a part of construction environmental sustainability. Hahn and Oluwatofumi (2021) examined adopting innovative technologies for sustainable real estate practice in Edo State, Nigeria.…”
Section: Smart Building Conceptsmentioning
confidence: 99%
“…In addition, Ahiabor (2019) also revealed that SBC needs better understanding by professionals to create a clear opportunity for real estate and developer adoption. Mensah (2016) also opined that awareness of smart buildings by professionals is still low because of a lack of knowledge on how to execute the concept of smart buildings, which is a part of construction environmental sustainability. Hahn and Oluwatofumi (2021) examined adopting innovative technologies for sustainable real estate practice in Edo State, Nigeria.…”
Section: Smart Building Conceptsmentioning
confidence: 99%
“…The environmental recovery rule favors contractors to embark on sustainable construction (Zs oka, 2008). Contractors' accumulation of knowledge and skills renders them more choices in implementing sustainable practices (Mensah et al, 2021). With the gathering of experience and knowledge in environmental recovery, contractors know better about the synthesis of antagonism, parasitism and mutualism along the construction process as explained using the theory of planned behavior (TPB).…”
Section: Contractors' Choices Of Unsustainable Constructionmentioning
confidence: 99%
“…Validation is applied in qualitative research to ensure that the results are valid and reliable (Mensah et al, 2021). In this study, an online workshop was conducted to verify the case study results.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation